Centratherum anthelminticum minimizes the risk of insulin resistance in fructose-induced type 2 diabetes - Hina Akram Mudassir, Shamim A. Qureshi (Journal of Applied Pharmaceutical Science, 2015)
The study was focused on investigating the effect of Centratherum anthelminticum ethanolic seed extract in fructose-induced type 2 insulin resistance diabetic rabbits after determining its qualitative analysis, acute toxicity, and effect on glucose tolerance. The phytochemical analysis revealed the presence of alkaloids, flavonoids, tanins, gallotannins, phlabotanins, phenols resins, saponins, and steroids. The same extract was found completely harmless up to 3000 mg/kg by showing no sign of acute toxicity in experimental rabbits. In oral glucose tolerance test, all doses (200-600mg/kg) of seed extract effectively produced percent reduction in blood glucose levels at 60 and 120 min. However, its high doses (400 and 600mg/kg) efficiently induced percent reduction (-10 to -11.9%) in post-prandial blood glucose level after 30 min as compared to diabetic control group. Similarly, the oral administration of same three doses (200-600 mg/kg) of extract for 14 days consecutively were found effective in decreasing blood glucose and serum total cholesterol, triglycerides, low- & very low-density lipoproteins while increasing high-density lipoprotein in fructose-induced type 2 diabetic test rabbits. In addition, fasting insulin resistance index (FIRI) was also decreased by normalizing insulin levels in these test groups as compared to fructose-induced type 2 diabetic control group (P
Keywords: Centratherum anthelminticum, Fructose, Insulin resistance, Type 2 Diabetes